Pelatihan Penulisan Skenario Film Untuk Siswa SMK Muhammadiyah 2 Pekanbaru - Muhammad Kafrawi; Evizariza; Raja Syamsidar (Fakultas Ilmu Budaya Universitas Lancang Kuning, 2020)
In modern times it is marked by the discovery of advanced technology, it requires a creative young generation, so that they can compete in accordance with the demands of the times. One of the areas of creativity that gets that place is creativity in creating films. Films can be used as a place to express feelings, as well as being used as a product promotion or area where the film's work is produced. This fact is strengthened by the increasing penetration of social media such as YouTube, Facebook, Twitter, and Instagram. To produce good film work, a reliable screenwriter is also needed. For this reason, training in writing film scenarios is required. This first stage scenario writing training was conducted at SMK Muhammadiyah 2 Pekanbaru. The younger generation, in this case, vocational high school students and the equivalent are a very potential age to be trained to write good and correct scenarios. With scenario writing training, at least SMK students can get to know what a scenario is and at the same time be able to practice writing good and correct scenarios.